IL-4 driven transcription factor FoxQ1 is expressed by monocytes in atopic dermatitis and stimulates monocyte migration - Ovsiy, Ilja; Riabov, Vladimir; Manousaridis, Ioannis; Michel, Julia; Moganti, Kondaiah; Yin, Shuiping; Liu, Tengfei; Sticht, Carsten; Goerdt, Sergij; Gratchev, Alexei; Kzhyshkowska, Julia (Scientific reports, 2017)
Monocytes are actively recruited at sites of chronic inflammation. However, molecular factors involved in this process are not fully elucidated. Here, we show that cytokine IL-4 which is implicated in the development of chronic inflammatory disease atopic dermatitis (AD) induces expression of transcription factor FoxQ1 in human monocytes and macrophages. FoxQ1 mRNA levels were elevated in monocytes of AD patients compared to healthy donors. Overexpression of FoxQ1 in RAW 264.7 monocytic cells facilitated their migration towards MCP-1 and was associated with decreased expression of migration-regulating genes (claudin 11 and plexin C1). Furthermore, FoxQ1 overexpression in RAW cells accelerated TNFα secretion after LPS challenge. Overall, our results indicate that FoxQ1 stimulates monocyte motility, increases pro-inflammatory potential, and directs monocyte migration towards MCP-1 that is crucial for monocyte influx into inflammatory sites. This mechanism could contribute to the pathogenesis of chronic inflammatory disorders such as AD.
Gesehen am 26.04.2018